(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Organizational Culture as a Factor in the Development of the Ecclesial Community, in the Context of Global Crises.Education is one of the fundamental pillars in affirming and protecting freedom and human rights in a society. Since human rights represent fundamental principles of human dignity and equality, it is essential to understand the importance of education as a factor in the development of society in general and the development of the ecclesial community in particular. Education can help change mindsets. Through education, society can learn about the importance of organizational culture, as well as the rinciples and values of the ecclesial community. In this article, the importance f organizational culture as a factor in the development of the ecclesial ommunity in the context of global crises will be particularly emphasized. Different types of organizational culture will be presented, as well as the importance of communication, freedom and human rights within society, in the context of global crises.